Dinamika Penegakan Hukum Pertambangan di Kabupaten Mandailing Natal: Antara Regulasi dan Realitas : (Studi Kasus di Kec. Kota Nopan, Kec. Huta Bargot, dan Kec. Batang Natal) - Budi Santoso; Pajriah Putri Islamy (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
Mining activities in Mandailing Natal Regency, particularly in Kota Nopan, Huta Bargot, and Batang Natal Districts, play a significant role in the local economy while simultaneously generating complex legal, environmental, and social problems. Despite the existence of comprehensive national regulations such as the Mineral and Coal Mining Law and regional bylaws, enforcement remains weak, as indicated by the persistence of illegal mining (PETI), environmental degradation, and conflicts of interest among various stakeholders. This study aims to analyze the dynamics of mining law enforcement by employing a juridical-empirical approach that combines the review of statutory regulations, secondary data, and field observations in three sample districts. The findings reveal that law enforcement is far from optimal due to structural constraints, including limited institutional capacity and inconsistent implementation, as well as cultural and economic factors, such as the community’s dependence on mining as a primary livelihood. Moreover, political and economic interests often weaken oversight and create selective enforcement, further widening the gap between regulation and practice. The study emphasizes that law enforcement in the mining sector should not rely solely on repressive measures but must be integrated with community empowerment, sustainable livelihood alternatives, and the strengthening of institutional governance. Therefore, reforming regional regulations, improving inter-agency coordination, enhancing law enforcement capacity, and ensuring active community participation are crucial steps to build legal, fair, and sustainable mining governance in Mandailing Natal.